REALITY CONSTRUCTION OF GUDANG SALT CIGARETTE ADVERTISING "CLIMBING" EDITION - Syafruddin Pohan; Agung Kurniawan Sastro; Asri Widyanti; Efri Ayu A. Br. Surbakti (Jurnal Scientia, 2023)
Reality can be said to be a social construction created by individuals. The mass media, as part of the individual, has a task based on the nature and fact of narrating events, so that all media content is nothing but constructed reality. News making in the media is basically the arrangement of realities to form a meaningful story or discourse. This scientific study presents an analysis in understanding the construction of reality by the mass media based on several theories from previous scientific studies. In this study, it is found that the message that is conveyed by the mass media is nothing more than a reality that has been constructed. The construction of messages in the mass media begins with the existence of facts or realities in society. These realities or facts can be objects, people, circumstances, events, ideas or behavior. These facts are then processed through a process called reality construction. This is the process of compiling data and facts into a meaningful story that can take the form of news.